Experimental design for testing and analysis of z-type self-expanding endovascular stents. (23rd June 2021) - Scott, Joel C.R.; Doman, Darrel A.; Johnston, Clifton R.
Stent migration and endoleak are common failure mechanisms for endovascular repair. Both can be partially attributed to a lack in understanding of the mechanical properties of endovascular stents. An alternative radial extensometer and machine vision system have been developed to both raise the quality of published radial force data, as well as to create and present an option for economical stent testing. The apparatus has shown promise as an accurate, repeatable, and reliable system for stent evaluation. Previous results by Johnston et al. examining z-type endovascular stents have been verified. Results showed that smaller stent diameters exhibit higher radial force than larger diameter stents, contrary to the expected outcomes due to increasing drag on increasing diameter stents. Stent orientation has been shown to contribute up to 8.8% error in radial force introduced by non-symmetrical brazed joints. The presence of a stent cover is shown to have negligible impact on stent radial force data above 10% reduction in area.